Fabrication of pH‐Responsive Hydrogel and Its In Vitro and In Vivo Evaluation - Tulain, Ume Ruqia; Ahmad, Mahmood; Rashid, Ayesha; Malik, Muhammad Zubair; Iqbal, Furqan Muhammad (Advances in polymer technology, 2018)
ABSTRACT The present research work deals with the development of pH‐responsive hydrogel by free radical polymerization in aqueous media to protect the rabeprazole sodium from acidic environment of stomach. Swelling behavior of hydrogels that was observed in buffer of various pH indicated highly pH‐dependent swelling of hydrogels. Characterization of pH‐responsive hydrogels by FTIR, SEM, and thermal analysis revealed that hydrogel has porous structure, favors swelling, drug loading, and drug release at a specific site in gastrointestinal tract and thermally more stable than parent polymer. In comparison with simple drug solution and hydrogel formulations, pharmacokinetic parameters of hydrogels formulations showed a significant difference in Cmax values of (CMC‐g‐AA) CA and the same oral dose of rabeprazole sodium was 87.28 ± 12.671 and 61.263 ± 5.37 ng/mL, respectively, Tmax of graft copolymer matrices CA (4.43 h) was significantly (P < 0.05) higher than drug solution (1 h) and area under curves (AUCs) for CA (952.25 ± 191 ng⋅h/mL) was significantly (P < 0.05) higher than the drug solution (83.67 ± 8.28 ng⋅h/mL) indicated the effect of dosage form would last for longer duration. Thus, in vitro and in vivo drug release studies of hydrogels proved their controlled release behavior with preferential delivery into alkaline pH environment and for a prolonged period of time.